COX-2 inhibitor delivery system aiming intestinal inflammatory disorders - Oliveira, Ana Isabel (2024)
Selective COX-2 inhibitors such as etoricoxib (ETX) are potentially indicated for the treatment of intestinal inflammatory disorders. However, their systemic administration provokes some off-site secondary effects, decreasing the desirable local effectiveness. To circumvent such limitations, herein an ETX delivery system based on electrospun fibrous meshes (eFMs) was proposed. ETX at different concentrations (1, 2, and 3 mg mL−1) was loaded into eFMs, which not affect the morphology and the mechanical properties of this drug delivery system (DDS). The ETX showed a burst release within the first 12 h, followed by a faster release until 36 h, gradually decreasing over time. Importantly, the ETX studied concentrations were not toxic to human colonic cells (i.e. epithelial and fibroblast). Moreover, the DDS loading the highest concentration of ETX, when tested with stimulated human macrophages, promoted a reduction of PGE2, IL-8 and TNF-α secretion. Therefore, the proposed DDS may constitute a safe and efficient treatment of colorectal diseases promoted by inflammatory disorders associated with COX-2.